STUDY ON CONSUMER ACCEPTANCE OF DRIED SMALL SHRIMP (Acetes erythraeus) FLOSS - Liza Kanafathy; Suparmi '; Dewita Buchari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The purpose of this research was to determine the consumer acceptance of dried small shrimp (Acetes erythraeus) floss and the best formulation in the processing of dried small shrimp floss and to know its nutrient. The method used was experimental method with T test to compare X1 treatments (meat floss seasoning) and X2 (fish floss seasoning). The parameter observed were organoleptic test and proximate test (content of moisture, protein and fat) and total bacteria plate count (TPC). The results showed that the the floss wich was made from meat seasoning (X1) was most preferable by consumers acceptance, wich charachteristics: golden brown and interested in appearance,   the seasoning and dried small shrimp has strongly smell, dry, smooth and compax texture, the flavor of seasoning and dried small shrimp was homogen, sweet taste. The product was contained moisture (5.67%), protein (35.98%), fat (9.99%), and the total bacterial colonies (1.22x104 cells/g). Keywords:Acetes erythraeus,consumer acceptance,shrimp floss